Electrosynthesized Ni-Al Layered Double Hydroxide-Pt Nanoparticles as an Inorganic Nanocomposite and Potentate Anodic Material for Methanol Electrooxidation in Alkaline Media - Biuck Habibi; Serveh Ghaderi (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2017)
In this study, Ni-Al layered double hydroxide (LDH)-Pt nanoparticles (PtNPs) as an inorganic nano-composite was electrosynthesized on the glassy carbon electrode (GCE) by a facile and fast two-step electrochemical process. Structure and physicochemical properties of PtNPs/Ni-Al LDH/GCE were characterized by X-ray diffraction, scanning electron microscopy, energy dispersive X-ray spectrometry and electrochemical methods. Then, electrocatalytic and stability characterizations of the PtNPs/Ni-Al LDH/GCE for methanol oxidation in alkaline media were investigated in detail by cyclic voltammetry, chronoamperometry, and chronopotentiometry measurements. PtNPs/Ni-Al LDH/GCE exhibited higher electrocatalytic activity than PtNPs/GCE and Ni-Al LDH/GCE. Also, the resulted chronoam-perograms indicated that the PtNPs/Ni-Al LDH/GCE has a better stability.